2022
DOI: 10.1029/2021jg006344
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Loss Pathways in Degraded Peatlands: New Insights From Radiocarbon Measurements of Peatland Waters

Abstract: Harden et al., 1992), so that the long-term accumulation of organic matter represents an important component of the terrestrial carbon cycle. However, peatlands are under widespread pressure with stressors, such as plantation forestry and agriculture (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 67 publications
(132 reference statements)
1
8
0
Order By: Relevance
“…That DOC is the youngest C form in these peatland inland water bodies follows previous 14 C studies on peatland streams, and rivers globally, where DOC is generally found to be modern (Billett et al, 2007(Billett et al, , 2012Dean et al, 2019;Evans et al, 2007Evans et al, , 2022Marwick et al, 2015;Tipping et al, 2010), except where there is clear disturbance within their catchments (Butman et al, 2015;Hulatt et al, 2014;Moore et al, 2013). DOC-F 14 C was positively correlated with DOC concentration in the Cross Lochs pools, indicating that increasing DOC concentrations may be driven by contemporary C inputs (Table S3).…”
Section: Peatland Pools Dominated By Contemporary Carbon But Old Carb...supporting
confidence: 79%
See 4 more Smart Citations
“…That DOC is the youngest C form in these peatland inland water bodies follows previous 14 C studies on peatland streams, and rivers globally, where DOC is generally found to be modern (Billett et al, 2007(Billett et al, , 2012Dean et al, 2019;Evans et al, 2007Evans et al, , 2022Marwick et al, 2015;Tipping et al, 2010), except where there is clear disturbance within their catchments (Butman et al, 2015;Hulatt et al, 2014;Moore et al, 2013). DOC-F 14 C was positively correlated with DOC concentration in the Cross Lochs pools, indicating that increasing DOC concentrations may be driven by contemporary C inputs (Table S3).…”
Section: Peatland Pools Dominated By Contemporary Carbon But Old Carb...supporting
confidence: 79%
“…This model conceptually follows empirical observations of both C accumulation and loss in peatland soils (Ratcliffe et al., 2018) and that discharge contributions to pools in blanket peatlands are mainly generated from near‐surface flow paths (Holden et al., 2018). We estimate the age contribution to each 14 C mixture (sample) based on reconstructed atmospheric 14 CO 2 which was assumed to be fixed into plant material and formed the organic matter in peat soils each year over the past 10,000 years by solving Equation (1) for λ (the rate parameter, termed “ k ” in e.g., Evans et al., 2022):F14Caq)(tgoodbreak=0infλeitalicλT0.25emF14Cair)(tgoodbreak−T0.25em2T5730italicdT,$$ {\mathrm{F}}^{14}{\mathrm{C}}_{\mathrm{aq}}(t)=\int_0^{\operatorname{inf}}\lambda {e}^{-\lambda T}\ {\mathrm{F}}^{14}{\mathrm{C}}_{\mathrm{air}}\left(t-T\right)\ {2}^{\frac{T}{5730}} dT, $$where F 14 C aq is sample 14 C content in F 14 C, F 14 C air is atmospheric 14 C‐CO 2 content at time ( t ), and T is the age of the sample in years before sampling date (yBSD). Atmospheric 14 CO 2 was derived from Reimer et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations